Hukum Keluarga Islam Sebelum dan Sesudah Kemerdekaan di Tunisia - Faozan, Ahmad (Socius: Jurnal Penelitian Ilmu-Ilmu Sosial, 2025)
Tunisia is one of the Muslim countries in the Maghreb region, North Africa. The capital of Tunisia is Tunis. Tunisia includes the Karkuana archipelago in the eastern region and the Djerba archipelago in the southeastern part. This study uses a qualitative approach to look at family law in Tunisia before and after independence. This study uses a historical approach. The source in this study was library data, analyzed qualitatively starting from data reduction, data presentation and drawing conclusions. After Tunisia became independent from the French Government then Tunisia’s Islamic Family Law was reformed and codified after the country gained independence. In the late forties, some leading Tunisian jurists thought that by performing a fusion of the Hanafi and Maliki schools, a new legal provision regarding family law could be developed adapted to the development of situations and social conditions in Tunisia. A group of jurists submitted a comparative account between the two systems of law, the Hanafi and the Maliki, and published it under the title Laihat Magazine al Ahkam al Syar’iyyah (Draft Code of Islamic Law). Finally, the government formed a committee under the supervision of the Islamic sheikh, Muhammad Ja'it, to draft a law officially derived from the Laihat and the Family Law Act of Egypt, Jordan, Syria and Ottoman Turkey. Government. The draft was finally invited under the title Magallah al Ahwal al Syakhsiyyah (Code Of Personal Status) 1956, contained 170 articles, 10 books and was invited throughout Tunisia on January 1, several times, namely through Law no. 70/1958, UU no. 41/1962, UU no. 1/1964, UU no. 77/1969, and the last one according to Tahir Mahmood’s records, underwent amendment in 1981 through Law No. 1/1981.